Environment and Offspring Surveillance in Porcine Brucellosis - Rebollada-Merino, Agustín; Pérez-Sancho, Marta; Rodríguez-Bertos, Antonio; García, Nerea; Martínez, Irene; Navarro, Alejandro; Domínguez, Lucas; García-Seco, Teresa (Frontiers in Veterinary Science, 2022)
Porcine brucellosis, caused by Brucella suis (B. suis), is a notifiable disease causing significant economic losses in production systems. Most infected pigs may act as carriers and shed B. suis even if asymptomatic. This can contribute to environmental persistence, thus hindering control efforts. Here, the environment and the offspring were investigated during and after a B. suis outbreak at a sow breeding farm. The diagnosis of B. suis in sows (n = 1,140) was performed by culture and polymerase chain reaction (PCR) from vaginal swabs, indirect enzyme-linked immunosorbent assay (I-ELISA) from sera, and brucellin skin test (BST). B. suis diagnosis in post-weaning pigs (n = 899) was performed by I-ELISA in sera and BST. The environmental surveillance programme was implemented by placing gauze sponges (n = 175) pre-hydrated in a surfactant and inactivating liquid for Brucella DNA detection by PCR in different farm areas. Our results showed that the offspring of infected sows reacted to in vivo techniques for B. suis. Furthermore, the offspring born during the outbreak displayed higher seropositivity (I-ELISA) and reactivity (BST) than those pigs born after. Brucella DNA was detected in pregnant sow areas, boxes, boots, and post-weaning pig areas. In addition, Brucella DNA environmental detection was higher during the B. suis outbreak than the post B. suis outbreak. The environmental approach has proven to be a simple, practical, valuable, and safe method to detect and monitor B. suis. These results suggest a role of the environment and the offspring that should be considered in porcine brucellosis surveillance and control programmes.